Psychosocial Assessment of Patients Undergoing Bone Marrow Transplant and Its Correlation with Transplant Outcome - Nabi Awan, Munazza; Shahbaz, Nighat; Hidayat, Irsa; Riaz, Sahla; Tariq, Hira; Toor, Saima Humayun (Pakistan Armed Forces Medical Journal, 2025)
Objective: To look at how the psychosocial factors impact outcomes of bone marrow transplant in transplant recipients, in a resource-limited country. Study Design: Cross-sectional study. Place and Duration of Study: Armed Forces Bone Marrow Transplant Centre, Rawalpindi, Pakistan from Jul 2022 to Jun 2023. Methodology: A total of 30 adult patients were included by non-probability Convenience Sampling, who underwent bone marrow transplant. Transplant outcome was measured in terms of hospital readmission rate, overall survival and disease-free survival at 90 days post-transplant. Pre-transplant Psychosocial assessment was done at time of admission for transplant prior to start of conditioning chemotherapy using Psychosocial Assessment of Candidates for Transplantation scale (PACT). Results: Out of total, 21 patients (70.0%) were male and 9 patients (30.0%) were female. Median age at time of transplant was 30.50(IQR: 20.75- 49.25) years. At follow up of 3 months OS was 87% (n=26, mean OS days= 81.20+4.14) and DFS was 83.0% (n=25, mean DFS days=69.04+4.66). Average duration of hospital stay was 20.53+ 9.58 day. All patients were low risk on HCT CI score. Higher Readmission rates were seen in patients (n=4, 13%) with lower PACT scores in domain of social stability. Higher final PACT score was significantly associated with improved OS and DFS. Conclusion: We concluded that patient’s psychosocial status can impact post HSCT outcome. Post transplant outcome and hospital readmission rate can be improved with good psychosocial support. Therefore, we recommend psychosocial assessment before ...